Improved Single-Cell Proteome Coverage Using Narrow-Bore Packed NanoLC Columns and Ultrasensitive Mass Spectrometry - Cong, Yongzheng (Anal Chem, 2020)
Single-cell proteomics can provide unique insights into biological processes by resolving heterogeneity that is obscured by bulk measurements. Gains in the overall sensitivity and proteome coverage through improvements in sample processing and analysis increase the information content obtained from each cell, particularly for less abundant proteins. Here we report on improved single-cell proteome coverage through the combination of the previously developed nanoPOTS platform with further miniaturization of liquid chromatography (LC) separations and implementation of an ultrasensitive latest generation mass spectrometer. Following nanoPOTS sample preparation, protein digests from single cells were separated using a 20 μm i.d. in-housepacked nanoLC column. Separated peptides were ionized using an etched fused-silica emitter capable of stable operation at the ~20 nL/min flow rate provided by the LC separation. Ultrasensitive LC–MS analysis was achieved using the Orbitrap Eclipse Tribrid mass spectrometer. An average of 362 protein groups were identified by tandem mass spectrometry (MS/MS) from single HeLa cells, and 874 protein groups were identified using the Match Between Runs feature of MaxQuant. This represents an >70% increase in label-free proteome coverage for single cells relative to previous efforts using larger bore (30 μm i.d.) LC columns coupled to a previous-generation Orbitrap Fusion Lumos mass spectrometer.